DISPUTE BOARDS: INOVAÇÃO NO GERENCIAMENTO DE CONFLITOS EM OBRAS DE CONSTRUÇÃO - Fernandes, Michelle Cristina Santiago (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Construction projects involve unique and complex products that depend on unclear variables and multiple agents, turning them into potential sceneries for the growth of conflicts. These disagreements, considered as inevitable and intrinsic to this productive environment, may become disputes when not solved, which may cause forfeiture of deadlines, results and expectations in a project. The increase of disputes at construction projects worldwide has stimulated the creation of methods for avoiding and settling disputes, alternatively to standard judicial proceedings. Highlights at this context are the Dispute Boards, which consist in committees that monitor the execution of big construction projects, in order to prevent and solve conflicts through recommendations and decisions. This work aims to present an overview of Dispute Boards, their modalities, characteristics, as well as the main cases in the world and the most known case in Brazil. Through the bibliographic review, s possible to notice that the adoption of Dispute Boards offers several benefits and that must be encouraged in the construction industry.